Collisional effects on the relativistic current-filamentation instability in dense plasmas. (March 2014) - Hao, B.; Sheng, Z.M.; Zhang, J.; Li, Y.T.
Abstract: Collisional effects on the current-filamentation instability (CFI), accounting for the space charge effect (SCE), are investigated kinetically for a relativistic beam propagating in dense plasmas. It is shown that collisions can completely suppress the SCE in low temperature dense plasma, leading to enhancement of the CFI. This kind of decoupling mechanism is quite different from the well-known resistive mechanism [Molvig (1975). Phys. Rev. Lett. 35, 1504]. In particular, we find the present decoupling mechanism can well explain the recent numerical simulation results [Karmakar et al. (2008). Phys. Rev. Lett . doi: 101, 255001]. In the parameter regime related to the laser-solid interaction and fast ignition scenario (FIS), the CFI growth rate with SCE included is enhanced in the low plasma density region through the decoupling mechanism. In the high plasma density region, it is enhanced mainly through the resistive mechanism.